(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the emotions related to learning of medical students at Dai Nam University in 2024. Research subjects and methods: Cross-sectional descriptive study surveying 274 medical students at Dai Nam University in 2024 via Google form. Results: The average score of positive emotions of students was 35.3 ± 8.0 points, of which the average score of positive emotions towards learning, class and exams was 10.7 ± 2.6 points, 10.6 ± 2.6 points and 14.0 ± 3.4 points. The average score of negative emotions is 35.6 ± 14.9, of which the average score of negative emotions towards class, studying and exams is 12.0 ± 5.8; 13.0 ± 5.4 and 10.6 ± 4.3 points, respectively. Conclusion: Negative emotions related to studying of medical students at Dai Nam University are at a low level while positive emotions are at an average level. The results suggest some intervention solutions for educational institutions to limit negative emotions and enhance positive emotions related to learning for students.